Item analysis of multiple choice questions of undergraduate pharmacology examinations in a medical college in Belagavi, Karnataka, India - Angadi, Netravathi B.; Nagabhushana, Amitha; Hashilkar, Nayana K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Multiple choice questions (MCQs) are a common method of assessment of medical students. The quality of MCQs is determined by three parameters such as difficulty index (DIF I), discrimination index (DI), and Distractor efficiency (DE). Item analysis is a valuable yet relatively simple procedure, performed after the examination that provides information regarding the reliability and validity of a test item. The objective of this study was to perform an item analysis of MCQs for testing their validity parameters. Methods: 50 items consisting of 150 distractors were selected from the formative exams. A correct response to an item was awarded one mark with no negative marking for incorrect response. Each item was analysed for three parameters such as DIF I, DI, and DE. Results: A total of 50 items consisting of 150 Distractor s were analysed. DIF I of 31 (62%) items were in the acceptable range (DIF I= 30-70%) and 30 had ‘good to excellent’ (DI >0.25). 10 (20%) items were too easy and 9 (18%) items were too difficult (DIF I <30%). There were 4 items with 6 non-functional Distractor s (NFDs), while the rest 46 items did not have any NFDs. Conclusions: Item analysis is a valuable tool as it helps us to retain the valuable MCQs and discard or modify the items which are not useful. It also helps in increasing our skills in test construction and identifies the specific areas of course content which need greater emphasis or clarity.